Acceptance and utilization of condoms in the prevention of HIV/AIDS amongst christian men in Mwinilunga - Lupili, Hellen Mulenga (Lusaka: University of Zambia , School of Medicine, 2005)
The main objective of the study is to determine the factors that influence the acceptance and utilization of condoms in the prevention of HIV/AIDS among christian men in Mwinilunga. The specific objectives are to determine the level of acceptance of condoms among christian men, determine the level of utilization of condoms among christian men, determine factors that influence the acceptance and utilization of condoms and make recommendations to all the concerned parties on how to increase condom use among christian men in order to prevent HIV/AIDS.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Nursing.
Includes bibliographical references.
Keywords: Condom use --Religious aspects --Christianity.; Condom use --Zambia.